Visual Analysis and the Contentious Politics of the Radical Right - Caiani, Manuela (Sociology compass, 2024)
ABSTRACT Although images are very important for political actors and social movements, including the radical right (RR), empirical studies still rarely integrate visual material as relevant data for understanding radical right politics. This article outlines this new and growing field of research (i.e., visuality and the RR), critically reviewing existing studies from the perspective of both visual studies of social movements and contentious politics, which are rarely applied to the RR, and the methodology of working with images, offering empirical case studies (European and beyond) to illustrate the argument. The findings reveal the main functions of the use of visuals for the radical right, as well as the benefits (but also the challenges) of studying radical right politics through the lens of visual analysis. A conceptual framework is proposed to capture this dominant visual politics of the radical right. As shown, two dimensions emerge as the most theoretically relevant for the radical right: The discursive meaning of images (the story itself, telling the story, eliciting the story) and the communicative function of images (visual expression by the movement or others, visibility), which combine agency and addressee.